Don’t Let it Happen Nor Let it Go: The Commitment of Peruvian Banking Institutions Against Money Laundering Through the Implementation of an AML Risk Assessment Methodologn - Haza Barrantes, Antonio de la (2018)
This article proposes the basic framework of what should be a methodology for identification and risk assessment in the prevention of money laundering for multiple operations companies, especially the banks that are part of the national financial system, with the objective of identifying those transactions that may be linked to asset laundering operations and should be subject to a suspicious transaction report to the Financial Intelligence Unit of Peru. At the same time, it highlights the role of banks as part of the economic structure of society, since they are the representative entities of the financial system, which is why they support people’s confidence in the integrity of the system. In this sense, the risk-based approach is analyzed from the perspective of a banking company, so that, in accordance with national and international regulations, they can reinforce the methodology for risk identification and evaluation, based mainly on the principle «know your costumer».